1997
DOI: 10.1007/s004649900513
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of malignant tumors missed at laparoscopic cholecystectomy

Abstract: The risk of missing coexisting diseases during laparoscopic operations has to be minimized by placing additional emphasis on careful evaluation of anamnesis. Physical examination and additional laboratory tests--such as analysis of tumor markers and blood in the stool--combined with complete abdominal ultrasonography, gastroscopy, and/or complete colonoscopy should be performed prior to LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Therefore, in this study it is appropriate to estimate the frequency of an apparently missed diagnosis of colorectal cancer as 2 (0.4%) in 473, which is concurrent with the incidence of 0.3%-0.7% of other reports. [5][6][7][8][9] With the widespread application of LC, surgeons may become inclined to neglect performing preoperative examination of the digestive tract before LC, even when it is indicated. Countering this pitfall, there is an opinion that examination of the digestive organs should be mandatory before LC; however, as the National Institutes of Health (NIH) consensus conference on gallstones and LC 16 indicated, patients with gallstones and atypical pain or dyspepsia need further investigation to determine the cause of their complaints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this study it is appropriate to estimate the frequency of an apparently missed diagnosis of colorectal cancer as 2 (0.4%) in 473, which is concurrent with the incidence of 0.3%-0.7% of other reports. [5][6][7][8][9] With the widespread application of LC, surgeons may become inclined to neglect performing preoperative examination of the digestive tract before LC, even when it is indicated. Countering this pitfall, there is an opinion that examination of the digestive organs should be mandatory before LC; however, as the National Institutes of Health (NIH) consensus conference on gallstones and LC 16 indicated, patients with gallstones and atypical pain or dyspepsia need further investigation to determine the cause of their complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a rare but undesirable complication of LC is missed intra-abdominal malignancies. According to the few reports on this subject, [4][5][6][7][8][9][10][11] the colorectum is the most frequent site of malignancies missed during LC. Furthermore, there is a recognized association between colorectal cancer and gallstones, [12][13][14] for which the majority of LCs are performed.…”
Section: Introductionmentioning
confidence: 99%
“…According to available publications and our data, 57 intra-abdominal malignancies diagnosed within several days to 28 days to 28 months after laparoscopic cholecystectomy have been reported [I, 3,4,9,10,12,17,18,19]. Most of these malignancies affected the elderly (mean age, 66.8 years), 55% of whom were women, whereas approximately 80% of the patients submitted to cholecystectomy are women.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be due to the loss of tactile sensation and the increased rate of LC, thus patients with atypical pain due to causes other than the gallstones are operated upon. [45][46][47] We had three female patients who presented within 2-3 months of LC with carcinoma of the stomach which was missed during previous endoscopy, a patient with cecal carcinoma who presented with acute small bowel obstruction, and another with rectal tumor who presented with rectal bleeding. Could these tumors have been diagnosed earlier if OC had been carried out instead of LC?…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in patients with atypical biliary pain, especially those over 50 years of age, investigations to exclude colonic tumors is necessary. [46][47] Major retroperitoneal vessel injury has been reported in 0.05% of these cases, 48 and bowel injury in 0.1%-0.3%. We experienced one case of each of the above complications, and the patient with vascular injury underwent laparotomy.…”
Section: Discussionmentioning
confidence: 99%